Effects of Eucalyptus camaldulesis aquatic leaf extract on Sorghum halapense seed germination, antioxidants enzyme and α-amylase enzyme activities - R. Farhoudi; F. Por Hassan (علوم و فناوری بذر ایران)
In order to evaluate the allelopatic potential of Eucalyptus camaldulesis aquatic extract on antioxidant enzyme activities, cell membrane damage and α-amylase enzyme activity of S. halapense, thisexperiments was conducted in Islamic Azad University, Shoushtar branch at 2012. The experiment was laid out according to a Completely Randomized Design with five replications and six treatments were various concentration of E. camaldulesis aquatic extract (0, 10, 20, 30, 40, 50 and 60%). The results indicated E. camaldulesis aquatic extract application exhibited gradual rise inhibitory effect on seed germination, seedling fresh weight, antioxidants enzymes activities, and α-amylase enzyme activity. Contrary to the previous traits, elevated malondialdehyde concentration and seedling fatty acid in S. halapense seedlings were detected. The minimum α-amylase enzyme activity (3.1 and 3.5  nmol prot -1 min-2 ), seedling fresh weight (0.1 and 0.8 mg) and seed germination (54% and 42 %) showed in 40% and 50% Eucalyptus camaldulesis aquatic extract.  The highest fatty acid (23.6% and 23.1%) was noted at 40% and 50% Eucalyptus camaldulesis aquatic extract. In conclusion, E. camaldulesis aquatic extract decreased seedling growth, α-amylase enzyme activity and cell membrane stability of S. halapense seedling.